Exploring hormone replacement therapy dynamics among menopausal women in Kuala Lumpur - a community based survey - Min Huei Gan; Muhammad Junaid Farrukh; Long Chiau Ming; Ganesh Sritheran Paneerselvam; Omotayo Fatokun; Susi Ari Kristina (BMC, 2024)
Abstract Background Women may lack awareness of the existence of Hormone Replacement Therapy (HRT), its benefits, and potential drawbacks. Furthermore, they may be uninformed about the treatability of menopausal symptoms. Consequently, there is a need to evaluate the knowledge, attitudes, and practices related to HRT among menopausal women within the Malaysian population. Presently, no studies have reported on the inside, attitudes, and practices regarding HRT among menopausal women in Kuala Lumpur. This study sought to determine the prevalence, knowledge, attitude, and practice (KAP) towards HRT and its association with socio-demographic characteristics of the study population. Method A cross-sectional study was conducted among menopausal women (n = 404) living in Kuala Lumpur, Malaysia. Data was collected using convenient sampling. This research consists of 5 major parts which are (A) Socio-demographic characteristics of participants, (B) HRT knowledge among respondents, (C) Attitudes towards HRT, (D) Practice of HRT, and (E) Menopausal symptoms. All appropriate data from the project was analyzed using IBM SPSS Statistics Ver 26. Results A total of 404 participants were recruited in this survey. Overall, participants had good knowledge (n = 254, 62.9%) and negative attitude (n = 213, 52.7%) towards HRT. The majority of them (83.4%) had never taken HRT. The common menopausal symptoms reported were hot flashes (35.4%), irritability/ mood swings (31.9%), and night sweats (29.2%). There was a significant association between knowledge of menopause and HRT and attitude towards HRT use. Participants (68.7%, n = 103) with poor knowledge of menopause and HRT showed a negative attitude towards HRT (p < 0.01). Conclusions Overall, the prevalence of HRT use among the respondents is low. 83.4% of them have never taken HRT before. There was a positive correlation between knowledge and attitude towards HRT use. Healthcare systems should educate the public using various educational tools and social media.